การประเมินศักยภาพของเทคนิค Time-Series InSAR เพื่อศึกษาการเคลื่อนตัวของรอยเลื่อนมีพลังขนาดเล็กในประเทศไทยและสาธารณรัฐแห่งสหภาพเมียนมาร์ - ปัทมา พอดี (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This research studies active faults motion using radar imageries. The First part is the study of interseismic motion of Sri Sawas fault group in Kanchanaburi province using 12 Radarsat-1 data by PSInSAR technique. The result reveals that motion’s standard deviations are around the same as the line-of-sight velocities of which are between -25.8 (toward the radar satellite) to 23.2 (away from the satellite) mm/yr, leading to the conclusion that the detected displacement velocities are not suitable for further study.The second section concerns the coseismic motions of Mw6.8 Tarlay earthquake occurring in western segment of Nam Ma fault in Myanmar. Four PALSAR images are processed by 2-pass DInSAR technique. Inversion of the resulted motions by single-patch model yields a fault slip of 2.5 m. while multi-patch model yields an average slip of 1.36 m. Using the 2.5 m slip from single-patch model results in the recurrence period between 1,040 to 4,160 years. Further, the computation of Coulomb stress change indicates the increasing stress of 0.6 bars in eastern segment of Mae Chan fault and 0.15 bars at Mae Ing and Chiang Kham fault.The last part of the studies determines postseismic motion of the Tarlay earthquake using 19 Radarsat-2 images by PSInSAR technique. The study detects LOS displacement rates between -24.3 and +34.5 mm/yr. The displacement pattern is consistent with that expected from postseismic motion. In addition, at Mae Chan fault, PSInSAR also shows velocities between –10 and +10 mm/yr, the pattern of which is consistent with deformation caused by interseismic motion.The coseismic study reveals the advantage of L-band radar imageries in the detection of active fault motion. On the contrary, PInSAR reveals limitations of C-band imageris as small number of PS and large standard deviation of the motions are produced, as evident in the study of interseismic motion in the tropical forest like Sri Sawas fault area.